Konsep Hard Skill, Soft Skill Dan Spiritual Skill Pustakawan Menghadapi Era Library 3.0 - Mohamad Rotmianto (IAIN Ponorogo, 2015)
In this present time, librarian must know well about information technology or it also called have a literacy of information technology. Because they (librarian) will face the “explosion of information”, as well as a new library user named “Net Generation” who wants all information to be presented more accurate, quicker and interactively, as the demands of Library 3.0. Mastery three skills: hard skill (IQ) and soft skill (EQ ) combined with spiritual skill (SQ) is required to succeed to be a Librarian 3.0, so not only qualifed in the feld of technology, but more than that librarians also have a humanism side that is based on religious principles.